I never left home : poet, feminist, revolutionary - Randall, Margaret, 1936- (Duke University Press, 2020)
"I NEVER LEFT HOME is a memoir by Margaret Randall, capturing details about her life as an American writer, activist, and academic who lived in Latin America for twenty-three years. Randall resettled in the United States in the eighties, after waging a successful five-year battle against deportation. The memoir, which chronologically charts her time in the United States, Mexico, Cuba, and Nicaragua, reproduces the meaning and feelings of particular eras and their cultures, politics, and everyday life. Poems and quotes from others, as well as some of her own creative work, are interspersed throughout the chapters, creating vivid images of places and people in time. After an introduction that explains how the book came to be, the chapters follow Randall's life trajectory chronologically. Chapter 1 explores Randall's family history and early days in New York during an era of Anti-Semitism and Jim Crow. She speaks of her parents, Jews who had settled in New York, and how hard they tried to escape their Jewishness, an internalized prejudice that would influence most of their family life. In chapters 2 and 3, Randall reminisces on her young adult years and, particularly, her encounters with poetry, art, and feminism during the ensuing Civil Rights era. Randall then writes extensively of the political, literary, and artistic landscape of Mexico City, her years amidst the Cuban Revolution, and her time with the Sandinistas in Nicaragua. The final chapter, "Home - 1984 and Beyond," maps her return to the mainland United States and her career as a professor. This book will be of interest to a general readership, but also to students and scholars in Latin American studies and cultural studies"--